Factors associated with mobility decrease leading to disability: a cross-sectional nationwide study in Japan, with results from 8681 adults aged 20-89 years - Keiko Yamada (BMC, 2021)
Abstract Background Mobility decrease leading to disability can gradually develop during early life, however, its related factors are not well clarified. Therefore, we investigate the related factors of mobility decrease at various levels, using nationwide data in Japan. Methods In total, 8681 independent community dwellers aged 20-89 years were analysed (average age, 51.6 years; 58.5% women). Three stages of mobility decrease were based on the locomotive syndrome risk test: Stage 1, emerging; Stage 2, progressing; Stage 3, progressed to restrict social engagement. Age was analysed using a simple quadratic function model. Results The prevalence of Stages 1-3 was 31.6% (n = 2746), 5.8% (n = 504), and 3.2% (n = 278), respectively. On the multivariable logistic regression, increased age in participants aged ≥40 years (stage 1: odds ratio[OR] 1.05-1.20, stage 2: OR 1.04-1.22, stage 3: OR 1.05-1.22), female (stage 1: OR 2.28, 95% confidence interval [CI] 1.99-2.61, stage 2: OR 2.40, 95% CI 1.77-3.25, stage 3: OR 1.80, 95% CI 1.19-2.72), overweight status (stage 1: OR 1.56, 95% CI 1.34-1.82, stage 2: OR 3.19, 95% CI 2.38-4.27, stage 3: OR 2.87, 95% CI 1.90-4.32), hypertension (stage 1: OR 1.20, 95% CI 1.01-1.41, stage 2: OR 1.99, 95% CI 1.49-2.64, stage 3: OR 2.10, 95% CI 1.44-3.05), and diabetes mellitus (stage 1: OR 1.62, 95% CI 1.17-2.24, stage 2: OR 1.57, 95% CI 0.93-2.66, stage 3: OR 2.10, 95% CI 1.13-3.90) were positively associated. The frequency of physical activity/sports, even a few per month, was inversely associated with all stages (stage 1: OR 0.59-0.72, stage 2: OR 0.50-0.67, stage 3: 0.36-0.53). A one-year increase in age had a stronger impact on mobility decrease in older adults than in younger ones. Increased age in participants aged < 40 years and smoking were associated with Stage 1, while intake of various foods was inversely associated with Stages 1 and 2. Conclusion Increased age (< 40 years) was associated with emerging mobility decrease, while that (≥ 40 years) was associated with any levels of mobility decrease. Female, lifestyle habits, including physical activities and overweight status, were associated with mobility decrease at every level.